PENGARUH KONDISI KEUANGAN, PERTUMBUHAN PERUSAHAAN DAN AUDIT TENURE TERHADAP KEMUNGKINAN PENERIMAAN OPINI GOING CONCERN DENGAN LEVERAGE SEBAGAI PEMODERASI - Darmansyah; Rahima, Tia; Ardiansyah, M (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
The aim of this research is to get empirical evidence the influence of financial conditions, company growth and audit tenure on the possibility of acceptance going concern opinion. The aim of this research is also to get empirical evidence of the influence of the company's financial condition and company growth the possibility of acceptance going concern opinion, when moderated by leverage. The data used in this research is secondary data on Manufacturing companies listed on the Indonesia Stock Exchange in the period of 2014-2017. Samples in this research are obtained by purposive sampling method. The method used to analyze the relationship between independent variables and the dependent variable is the logistic regression method. The results of the research showed that the variable financial condition significantly influenced on the acceptance of going concern opinion. While the company's growth and audit tenure variables do not affect the going concern audit opinion. The results of the research also showed that the leverage variable, which is a moderating variable, cannot moderate the relationship of the company's financial condition and the company's growth towards the possibility of accepting going-concern audit opinion.